Let bees be bees - Norman A. Johnson (Evolution: Education and Outreach, 2020)
Abstract Thomas Seeley reviews a half century of research, mostly conducted by himself and his colleagues on the ecology, evolution, and natural history of wild honey bees. He provides insights into how bees reproduce, how they forage, and how they defend the colony. The final chapter, “Darwinian beekeeping” discusses how ecological and evolutionary principles can be incorporated into the practice of beekeeping.